2021
DOI: 10.3390/v13112309
|View full text |Cite
|
Sign up to set email alerts
|

How Influenza A Virus NS1 Deals with the Ubiquitin System to Evade Innate Immunity

Abstract: Ubiquitination is a post-translational modification regulating critical cellular processes such as protein degradation, trafficking and signaling pathways, including activation of the innate immune response. Therefore, viruses, and particularly influenza A virus (IAV), have evolved different mechanisms to counteract this system to perform proper infection. Among IAV proteins, the non-structural protein NS1 is shown to be one of the main virulence factors involved in these viral hijackings. NS1 is notably able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 347 publications
(435 reference statements)
0
16
0
Order By: Relevance
“…Alternatively, IFITM1, an interferon-induced transmembrane protein, is signi cantly upregulated by IFN-β stimulation. IFITM1 was proven to be more effective in resisting the in uenza virus infection by blocking the fusion of the viral particle with the cellular host membrane during the uncoating step [34,35]. TRIM22 expression is also upregulated by IFN-β in response to IAV infection and has been reported to be a marker of activation of the type I IFN system in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, IFITM1, an interferon-induced transmembrane protein, is signi cantly upregulated by IFN-β stimulation. IFITM1 was proven to be more effective in resisting the in uenza virus infection by blocking the fusion of the viral particle with the cellular host membrane during the uncoating step [34,35]. TRIM22 expression is also upregulated by IFN-β in response to IAV infection and has been reported to be a marker of activation of the type I IFN system in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we detected for both, GAS mono-infection and superinfection an upregulation of Il1b, which suggests that the incapacity of co-infected macrophages to process and secrete IL-1β is due to a failure in the GAS-inducible activation of the NLRP3 inflammasome [86][87][88][89]. In fact, it was shown that different variants of IAV, including a 2009 pandemic strain, were capable of thwarting IL-1β maturation by interfering with NLRP3 inflammasome assembly [90][91][92], which is crucial for innate immune sensing and coordination [93]. An IAV-mediated nullification of IL-1β secretion would be of dramatic consequences during streptococcal superinfections.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some viruses have developed strategies to evade the host innate immune response that involve the activation of various pattern recognition receptors (PRRs), including toll-like receptors (TLRs), among others, and the subsequent signaling resulting in the production of proinflammatory cytokines and/or the activation of programmed cell death [ 114 , 117 , 118 , 120 , 127 , 128 , 129 ]. For example, IAV is recognized by various PRRs, depending on the cellular compartment, the different types of cells, and the different stages of infection [ 130 ], and may also trigger PRR activation mechanisms to subvert the innate immune response [ 131 , 132 ]. Indeed, TRL activation leading to autophagy and apoptosis is subverted by IAV to enhance virion stability [ 133 , 134 , 135 ] and to facilitate its replication [ 136 ].…”
Section: Aid Of Cathepsins To Viruses In the Host Cell Infectionmentioning
confidence: 99%